Relationship between stress, anxiety, and depression with suicidal ideation in adolescents - Heni Dwi Windarwati; Retno Lestari; Satrio Agung Wicaksono; Mira Wahyu Kusumawati; Niken Asih Laras Ati; Shofi Khaqul Ilmy; Ari Dwi Sulaksono; Desi Susanti (Universitas Airlangga, 2022)
Introduction: Suicide is a significant mental health problem in adolescents around the world that requires comprehensive treatment. This study aimed to examine the relationship between stress, anxiety, and depression with suicidal ideation in adolescents. Method: This research used quantitative methods with a cross-sectional approach. The number of respondents was 869 adolescents, with a total sampling technique. The instrument used to measure stress, anxiety, and depression is the Depression Anxiety Stress Scale (DASS-21), while the idea of suicide is measured using the Scale for Suicide Ideation (SSI) instrument. Results: The result of this study showed that teenagers who had suicidal ideation were 206 (23.7%) respondents, while 663 (76.3%) of other respondents did not have the idea of suicide. There was a significant relationship between suicidal ideation with stress levels (p-value 0.000), anxiety (p-value 0.000), and level of depression (p-value 0.000) in adolescents. Conclusion: Mental and psychological health support measures must be given to adolescents to prevent an increase in suicide ideas.